2021
DOI: 10.3390/admsci11040136
|View full text |Cite
|
Sign up to set email alerts
|

When COVID-19 Is the Invader and Internal Communication Is the Hero: Understanding the Influence of Internal Communication on Individual Performance and Evaluating the Mediating Role of Perceived Support

Abstract: Objective: The main objective of this study was to evaluate the impact of internal communication (IC) of organisations on the quality of the individual–organisation relationship, specifically with regard to the effects generated with respect to individual performance (IP) in a pandemic framework. In this sense, the study intends to evaluate the effects of IC on the employee’s IP, having as a mediator perceived organisational support (POS). Methodology: To achieve the aforementioned objectives, a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…Therefore, this study is in line with other studies previously conducted that found a relationship between symmetric internal communication and organizational identification (Sun et al 2021;Yue et al 2021). It can also be found that adopting practices geared towards good internal communication can improve employee performance in the organization (Ahmed and Rafiq 2002;Latham et al 2002;Gomes et al 2021Gomes et al , 2023.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, this study is in line with other studies previously conducted that found a relationship between symmetric internal communication and organizational identification (Sun et al 2021;Yue et al 2021). It can also be found that adopting practices geared towards good internal communication can improve employee performance in the organization (Ahmed and Rafiq 2002;Latham et al 2002;Gomes et al 2021Gomes et al , 2023.…”
Section: Discussionsupporting
confidence: 91%
“…Taking a closer look, the second contribution concerns the understanding of how employees can be one of the most significant work forces in the routine of organizations, since their attitudes affect both individual productivity and business effectiveness (Men and Stacks 2014;Gomes et al 2021). This study brings clarification to organizations regarding the benefits of implementing internal communication actions through human resource management.…”
Section: Theoretical Contributions and Implications Of The Studymentioning
confidence: 97%
See 2 more Smart Citations
“…Organizational studies are quite wide in terms of research interests for studies into the employee-organization relationship (e.g., Duarte et al 2019;Ribeiro et al 2020a;Balaskas et al 2020;Gomes et al 2021;Wiefek and Heinitz 2021). Within the wide plethora of relevant and current remits of investigation, the subjects of avoiding turnover intention and stimulating employee performance present themselves as key matters for promoting organizational success.…”
Section: Discussionmentioning
confidence: 99%